Field study on visual and cognitive stressors in Visual Display Terminal office work - Rodriguez, Roberto Germán (2014)
Office Visual Display Terminal (VDT) work is a paradigmatic case of a work system in which the adoption of a new technology introduces new associated risks of different natures: visual, musculoskeletal and cognitive. We carried out a Post Occupancy Evaluation at University of Mendoza administrative offices, and made a diagnosis of visual, cognitive and postural risks associated with VDT office work. Our results showed levels of horizontal illuminance lower than the legally required by our legislation, whose regulations need to be revised and updated. We found that 32% of our participants were outside the acceptable range of mental workload. Also, we explored the hypothetical role of glare sources as environmental distractors, finding a statistically significant linear correlation between vertical illuminance level and Stroop interference. This exploratory study described the behavior of many variables of interest in actual work situations, allowing us to propose a general model of VDT office.